Charcot Collapse: Does Collapse Pattern Dictate Osseous Metabolism?. Issue 5 (October 2017) - Grant, Lisa; Yoho, Robert; Halaharvi, Chandana; Grant, William
Charcot fracture pattern (FP) and Charcot dislocation pattern (DP) are 2 distinct collapse patterns identified in Charcot neuroarthropathy of the foot and ankle. These patterns are believed to demonstrate relative differences in central bone mineral density (BMD), which has been theoretically extrapolated to describe local BMD. To assess variation in local bone composition of FP and DP patients, 10 patients, 5 DP and 5 FP were recruited. The patient's age, body mass index (BMI), radiographs, central BMD, local BMD, sRANKL (soluble receptor activator nuclear factor kappa-beta ligand), sRAGE (soluble receptors of advanced glycated end-products), and osteocalcin were measured to determined bone metabolic status and density. Central BMD was determined using DEXA (dual-energy X-ray absorptiometry) scans of the hip. peripheral BMD was determined using scans at the level of the ankle mortise and Chopart's joint, depending on the location of collapse. These scans were then compared with controls. Central and peripheral DEXA scans were significantly reduced in the FP ( P = .002 andP < .0001) when compared with healthy controls. Additionally, FP patients demonstrated statistically significant elevations in sRANKL ( P = .05) and sRAGE ( P = .002) when compared with DP. No significant difference was seen in osteocalcin ( P = 0.22); however, elevated values compared with normal reference ranges suggest increase bone production. These elevations combined with an osteoporotic profile may indicate difficulty of FP patients in repairing micro fracture. Results from this study emphasize the increased risk of nonunion during FP reconstruction, and highlight the variation in bone composition in these 2 Charcot subtypes. Levels of Evidence: Level III